Acquired idiopathic generalized anhidrosis - Geethu Gangadharan; Sebastian Criton; Divya Surendran (Wolters Kluwer Medknow Publications, 2015)
Acquired idiopathic generalized anhidrosis is a rare condition, where the exact pathomechanism is unknown. We report a case of acquired idiopathic generalized anhidrosis in a patient who later developed lichen planus. Here an autoimmune-mediated destruction of sweat glands may be the probable pathomechanism.